Disentangling the resistant mechanism of Fusarium wilt TR4 interactions with different cultivars and its elicitor application - Zhou, Guang-Dong; He, Ping; Tian, Libo; Xu, Shengtao; Yang, Baoming; Liu, Lina; Wang, Yongfen; Bai, Tingting; Li, Xundong; Li, Shu; Zheng, Si-Jun (Frontiers in Plant Science, 2023)
Fusarium wilt of banana, especially Tropical Race 4 (TR4) is a major factor restricting banana production. Developing a resistant cultivar and inducing plant defenses by elicitor application are currently two of the best options to control this disease. To determine the control effect of elicitor isotianil on TR4 in different resistant cultivars, a greenhouse pot experiment was conducted and its results showed that isotianil could significantly alleviate the symptoms of TR4, provide enhanced disease control on the cultivars ‘Baxi’ and ‘Yunjiao No.1’ with control effect 50.14% and 56.14%, respectively. We compared the infection processes in ‘Baxi’ (susceptible cultivars) and ‘Yunjiao No.1’ (resistant cultivars) two cultivars inoculated with pathogen TR4. The results showed that TR4 hyphae could rapidly penetrate the cortex into the root vascular bundle for colonization, and the colonization capacity in ‘Baxi’ was significantly higher than that in ‘Yunjiao No.1’. The accumulation of a large number of starch grains was observed in corms cells, and further analysis showed that the starch content in ‘Yunjiao No. 1’ as resistant cultivar was significantly higher than that in ‘Baxi’ as susceptible cultivar, and isotianil application could significantly increase the starch content in ‘Baxi’. Besides, a mass of tyloses were observed in the roots and corms and these tyloses increased after application with isotianil. Furthermore, the total starch and tyloses contents and the control effect in the corms of ‘Yunjiao No.1’ was higher than that in the ‘Baxi’. Moreover, the expression levels of key genes for plant resistance induction and starch synthesis were analyzed, and the results suggested that these genes were significantly upregulated at different time points after the application of isotianil. These results suggest that there are significant differences between cultivars in response to TR4 invasion and plant reactions with respect to starch accumulation, tyloses formation and the expression of plant resistance induction and starch synthesis related genes. Results also indicate that isotianil application may contribute to disease control by inducing host plant defense against TR4 infection and could be potentially used together with resistant cultivar as integrated approach to manage this destructive disease.